Science Capital and Science Museums: Review of a CIMUSET session in the General Conference of ICOM 2022 (London Journal of Research In Humanities and Social Sciences, 2023)
What are the potentials and challenges for science museums to promote equity and justice from a science capital perspective? This was the theme of one of the CIMUSET sessions during the ICOM Conference in 2022. This review presents highlights from the panelists' presentations and the discussion afterward. The session demonstrates that museums recognize the accessibility, inclusion, and diversity relevant. However, there is little concrete evidence of practice — especially regarding including people with disabilities. At the same time, it highlighted weaknesses and sensitive topics, lessons learned, opportunities to be explored, and a field of practice and research to be deepened.
Keywords: science communication; science centers and museums; social inclusion